Mathematics study habits through an ethnomathematics approach and entrepreneurial behavior of mathematics education students - Anggoro, Abdurrobbil Falaq Dwi; Widada, Wahyu; Nugroho, Khathibul Umam Zaid; Herawaty, Dewi; Jumri, Rahmat; Anggoro, Shadaqnas Dewarif Tri; Alias, Norma; Ismoen, Muhaimin (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
This research aims to determine whether there is a positive correlation between mathematics learning habits through an ethnomathematics approach and entrepreneurial behavior. This research is survey research conducted by mathematics education students in Bengkulu and Lubuklinggau. The sample for this research consisted of 70 students. There are two questionnaires as research instruments. Both are a questionnaire on mathematics learning habits using an ethnomathematics approach, and an entrepreneurial behavior questionnaire. The result of this research is that the complete structural equation model fit test is a good fit, which means that the empirical structural equation model is suitable with the theoretical (conceptual) structural equation model. The results of the hypothesis test show that the calculated t value is 11.364 > 1.96, which means Ho is rejected, meaning that this research hypothesis is accepted. The conclusion is that there is a positive correlation between mathematics learning habits through an ethnomathematics approach and entrepreneurial behavior.